Rancang Bangun Software Defined Radio (SDR) pada Frekuensi Multiband 88 MHz sampai dengan 800 MHz untuk Sistem Penerima Audio berbasis Raspberry - Heroe Wijanto; Budi Herdiana; Yudha Eko Bimantoro (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2019)
Abstract – Technology radio communication is currently developing, initially SDR (Software Defined Radio) is used by amateur radio to communicate , but with the presence of the SDR technology will have a major influence on technological development in the field of radio communication. SDR technology can replace several devices in a certain frequency range and mode, especially on military tactical equipment, so that it has a light weight, smaller dimensions and is reconfigurable in addition to this (multiband). In the future this technology will be very necessary to overcome various kinds of obstacles in many of these things. Because of that Software Defined Radio (SDR), problems in the technology platform can be easily other than that in terms of education its use can facilitate learning about the system general radio communication. Keywords : Software Defined Radio (SDR), reconfigurable, multiband